Draft genomes and genomic divergence of two Lepidurus tadpole shrimp species (Crustacea, Branchiopoda, Notostraca). (19th October 2018) - Savojardo, Castrense; Luchetti, Andrea; Martelli, Pier Luigi; Casadio, Rita; Mantovani, Barbara
Abstract: Crustaceans of the order Notostraca (Branchiopoda) are distributed worldwide and are known for the remarkable morphological stasis between their extant and Permian fossil species. Moreover, these crustaceans show relevant ecological traits and a wide range of reproductive strategies. However, genomic studies on notostracans are fairly limited. Here, we present the genome sequences of two notostracan taxa, Lepidurus arcticus and Lepidurus apus lubbocki . Taking advantage of the small genome sizes (~0.11 pg) of these taxa, genomes were sequenced for one individual per species with one run on the Illumina HiSeq X platform. We finally assembled 73.2 Mbp ( L. arcticus ) and 90.3 Mbp ( L. apus lubbocki ) long genomes. Assemblies cover up to 84% of the estimated genome size, with a gene completeness >97% for both genomes. In total, 13%–16% of the assembled genomes consist of repeats, and based on read mapping, L. apus lubbocki shows a significantly lower transposable element content than L. arcticus . The analysis of 2, 376 orthologous genes indicates an ~7% divergence between the two Lepidurus taxa, with a nucleotide substitution rate significantly lower than that of Daphnia taxa. K a /K s analysis suggests purifying selection in both branchiopod lineages, raising the question of whether the low substitution rate of Lepidurus is correlated with morphological conservation or is linked to specific biological traits. Our analysis demonstrates that, in these organisms, it is possible to obtain high‐quality draft genomes from single individuals with a relatively low sequencing effort. This result makes Lepidurus and Notostraca interesting models for genomic studies at taxonomic, ecological and evolutionary levels.